The path that Allah made: quran stories for little hearts - Khan, Saniyasnain (Goodword Books India, 2002)
This story follows a character's journey along a path created by Allah, illustrating how faith guides one's steps through life's challenges. It emphasizes the importance of trusting in God's plan and recognizing the blessings that come from staying true to one$1 (Bs beliefs, even when faced with obstacles.s